SPATIAL DISTRIBUTION OF VS30 BASED ON MASW AND MICROTREMOR INVERSION IN GUNUNGKIDUL, YOGYAKARTA, INDONESIA - Wijayanto, Wijayanto; Mardiatno, Djati; Daryono, Daryono; Nehren, Udo; Marfai, Muh Aris; Pramono, Sigit (GEOMATE International Society, 2022)
Gunungkidul Regency, Yogyakarta, is one of the earthquake-prone areas in Java. Hazard assessments are necessary to create an earthquake risk map for the area. An earthquake hazard assessment can be performed by identifying the site conditions from the average value of the shear wave velocity to a depth of 30 meters (Vs30). This research aims to analyze the spatial distribution of Vs30 in the Gunungkidul region. We collected 98 microtremors and MASW from site surveys and previous studies. The data inversion was done to obtain a one-dimensional (1D) Vs30 model and estimate the Vs30 value. The results are presented in the Vs30 spatial distribution map and site classification. They show that the value of Vs30 is mostly high, with a range of 355 – 1092 m/s. The site classification is in the very dense soil or soft rock (SC) to rock (SB). The Vs30 value tends to be higher than the United States Geological Survey (USGS), especially in the karst plateau area, which has a gentle slope, where the site class was SC while the USGS was stiff soil (SD). Based on the landform analysis, fluvial landforms have low Vs30 with an average of 437 m/s. However, karst and structural landforms have high Vs30 with an average of 713 m/s and 691 m/s, respectively. The difference in these values indicates that local conditions significantly affect the Vs30. This study benefits disaster mitigation and serves as the basis for regional development based on earthquake risk reduction © Int. J. of GEOMATE All rights reserved, including making copies unless permission is obtained from the copyright proprietors